The Relationship between Coping Strategies and Academic Adjustment with Academic Stress of Students during COVID-19 Online Learning Pandemic - Primadasa, Arizal; Raihana, Permata Ashfi (Universitas Muhammadiyah Surakarta, 2022)
The online learning resulting from the COVID-19 pandemic has caused various problems that have led to academic stress among students. The purpose of this research is to investigate the relationship between coping strategies and academic adjustment with academic stress among students during online learning in the COVID-19 pandemic. The subjects of this study were 230 students from the 2018 and 2019 classes of the Psychology Faculty of Muhammadiyah University Surakarta who have transitioned from offline to online learning, selected using purposive sampling technique. The method used in this research is quantitative correlational. Multiple regression analysis was used to analyze the data. The results of this research indicate a significant correlation between coping strategies and academic adjustment with academic stress (R=0.368, sig=0.000). The effective contribution of coping strategies and academic adjustment to academic stress was 13.6%.